Effect of partially reduced highly fluxed DRI pellets on impurities removal during steelmaking using a laboratory scale EAF - Dishwar R.K.; Sinha O.P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present work represents a comparative study on the impurities removal from pig iron melt by addition of partially reduced highly fluxed direct reduced iron (DRI) to make steel in a 2 kg capacity electric arc furnace (EAF). Three types of fluxed DRI (30, 50, 80% Reduction (%R) with similar basicity-8) were used to maintain different level of oxidizing potential on the bath for studying the kinetic behavior of impurities removal from melt. Results showed that the rate of removal of impurities (i.e. C, Si, Mn, P, S etc.) increased initially up to 5 minutes of reaction time then decreased afterwards. Phosphorus (~64%), sulfur (~16%), and carbon (~94%) were removed simultaneously up to 25 minutes of reaction time using 30%R fluxed DRI. Similarly, phosphorus (~33%), sulfur (~50%), and carbon (~62%) were removed simultaneously using 50%R fluxed DRI while highly reduced (80%R) flux DRI removed sulfur (~58%), carbon (~56%) with a small fraction of phosphorus (~18%) from pig iron. It was observed in all the cases that silicon (>99%) and manganese (>80%) were removed. From the present study, it can be concluded that ~30%R DRI is favorable for effective phosphorus removal whereas ~80%R is favorable for sulfur removal. The significant removal of impurities could be achieved by charging ~50%R fluxed DRI in the pig iron melt.